2016
DOI: 10.1158/0008-5472.can-15-2308
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA-Binding Protein LARP4B as a Tumor Suppressor in Glioma

Abstract: Transposon-based insertional mutagenesis is a valuable method for conducting unbiased forward genetic screens to identify cancer genes in mice. We used this system to elucidate factors involved in the malignant transformation of neural stem cells into glioma-initiating cells. We identified an RNAbinding protein, La-related protein 4b (LARP4B), as a candidate tumor-suppressor gene in glioma. LARP4B expression was consistently decreased in human glioma stem cells and cell lines compared with normal neural stem c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 42 publications
2
53
1
Order By: Relevance
“…Moreover, we found that stomach adenocarcinoma (STAD) tends to have disproportionately higher number of NMD-elicit mutations and a mutator phenotype that selects for NMD-elicit mutations in LARP4B, EIF5B and PTEN . Although the potential relationship between LARP4B or EIF5B and cancer has been previously reported31323334, the link between these genes and hypermutation was previously unrecognized. It is conceivable that NMD-mediated hypofunction of LARP4B or EIF5B permits the hypermutated cancer cells to cope with a high mutation load by delaying translation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that stomach adenocarcinoma (STAD) tends to have disproportionately higher number of NMD-elicit mutations and a mutator phenotype that selects for NMD-elicit mutations in LARP4B, EIF5B and PTEN . Although the potential relationship between LARP4B or EIF5B and cancer has been previously reported31323334, the link between these genes and hypermutation was previously unrecognized. It is conceivable that NMD-mediated hypofunction of LARP4B or EIF5B permits the hypermutated cancer cells to cope with a high mutation load by delaying translation.…”
Section: Discussionmentioning
confidence: 99%
“…LARP4B has been found to act as a tumor suppressor and oncogene, possibly dependent on the type of cancer, e.g., solid or blood. LARP4B was identified as a tumor suppressor by a genetic screen in mice and more recently characterized in human glioma cells (for more comprehensive review see Ref ). Overexpression of LARP4B induced apoptosis and mitotic arrest, partially dependent on the La module suggesting that interaction with RNA and its other interacting proteins is important .…”
Section: Recent Advances On Larp4 Family Membersmentioning
confidence: 99%
“…Overexpression of LARP4B induced apoptosis and mitotic arrest, partially dependent on the La module suggesting that interaction with RNA and its other interacting proteins is important . Knockdown of LARP4B in primary mouse astrocytes lacking p53 and Nf1 promoted cell proliferation, tumor size, and invasiveness . In a study of an acute myeloid leukemia mouse model, LARP4B was found to act as an oncogene …”
Section: Recent Advances On Larp4 Family Membersmentioning
confidence: 99%
“…Some members of this superfamily, such as LARP1 [169][170][171][172] and LARP6 [173], control the expression of target transcripts and promote the progression of several cancer types. On the other hand, LARP4A [174] and LARP4B [175] are tumor-suppressive RBPs, which inhibit cancer metastasis and growth, respectively.…”
Section: Rna-binding Proteins (Rbps) the Silent Guardians Of The Tramentioning
confidence: 99%